UMPSA celebrates 22 years of collaboration networking with media and partners at Iftar Ceremony - Naqiah, Puaad (UMPSA, 2024)
KUANTAN, 2 April 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) celebrated nearly 100 media representatives and partners at the Iftar Ceremony in conjunction with 22 years of close collaboration.